Metric evidence of the scale of perceived fear related to the covid-19 pandemic in adults from Tacna - Vargas Vargas, Daniza del Rosario (2021)
The present research aimed to identify the metric evidences of the scale of perceived fear related to the covid-19 pandemic in adults from Tacna, 2020. The research was instrumental, a non-probabilistic sampling was carried out for convenience, with the participation of 157 adults from the city of Tacna, whose age ranged from 20 to 59 years, being 68.2% female and 31.85% male. The fear scale related to the covid-19 pandemic (FCV-19S) of Ahorsu et al. Was used. (2020) and the collection of information was virtual. The results indicate that the fear scale in its original proposal is one-dimensional but that at the time of translating it into Spanish it is convenient to treat it as twodimensional because the first does not present good adjustment indices, on the other hand the new proposal does present them in such a way which is concluded that it has good construct validity (X2 / gl = 3.286; CFI = 0.943; GFI = 0.926; TLI = 0.907; SRMR = 0.0504). This proposal was chosen (AIC = 72,712) when comparing it with two others that did not reach the optimal criteria. The adjustment index of the bifactorial proposal presented evidence of construct validity and with adequate bifactor model indices (X2 / gl = 1.713, CFI = 0.992, GFI = 0.981, TLI = 0.971, SRMR = 0.0260; wh = 0.703; Hng = 0.955); although the ECV = 0.521 and PUC = 0.571 were low. However, it should be tested in future research. The scale presents an ordinal alpha of 0.856 and an omega coefficient = 0.836, showing that the instrument has high reliability. The study reports that the Spanish version of the FCV-19S applied to the population of Tacna, Peru, demonstrated a bifactor model with adequate psychometric properties. Therefore, it is recommended to use it within the general population.